2018
DOI: 10.1093/asj/sjy209
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Plastic Surgeons’ Social Media Use and Perceptions

Abstract: Professional social media use is rising within plastic surgery. However, a dichotomy exists in acceptance. Private practice, younger surgeons are more likely to view social media as an acceptable method of reaching patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 14 publications
2
60
0
Order By: Relevance
“… 7 Another study found that 61.9% of plastic surgeons had active professional social media accounts. 6 Among colorectal surgeons, only 37.1% had LinkedIn profiles. 20 Comparing our findings with these studies suggests that in general professional team physicians may have greater rates of social media use than physicians not affiliated with a professional sports team.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 7 Another study found that 61.9% of plastic surgeons had active professional social media accounts. 6 Among colorectal surgeons, only 37.1% had LinkedIn profiles. 20 Comparing our findings with these studies suggests that in general professional team physicians may have greater rates of social media use than physicians not affiliated with a professional sports team.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported that private practice physicians have greater social media use relative to physicians in academic medicine. 6 , 7 , 22 One possible explanation for this disparity is that, given the high overall levels of social media use among professional sport team physicians, differences between private and academic physicians are subtler and thus more difficult to measure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with fields outside of ophthalmology as demonstrated in a survey of plastic surgeons and a review of neurosurgery social media accounts. 11,12 Further, ophthalmologists working in a private practice in any capacity were more likely to use social media with the intention of publicizing their practice. This observation matches the recent abundance of literature regarding leveraging social media platforms to connect with and potentially draw patients to practices.…”
Section: Discussionmentioning
confidence: 99%